Content Analysis of Da'wah Messages in Revealing the Defense of Palestine on @Felixsiauw's YouTube Account - Lubis, Chaerona Artha; Kholil, Syukur (Golden Ratio of Social Science and Education, 2024)
This study aims to reveal the content of da'wah messages in voicing the defense of Palestine which includes aqidah, sharia and ahlak contained in Ustadz Felix Siauw's da'wah material in his YouTube account with the title "The War Is Not Only In Gaza, But Also In Our Heads". This research uses Critical Media theory where social media can be used as a forum for sharing knowledge to free humans, especially the small and poor people from the oppressive system structure such as the people in Palestine. This research method uses a descriptive qualitative approach that describes a message or text in detail until the results are found in the form of words not numbers. Primary data in the study were obtained from the transcripts of Ustad Felix Siauw's lectures and secondary data were taken from related journals and articles. Data collection techniques using observation and documentation, with Hermeneutic analysis techniques convey and translate God's messages into a more understandable language. The results obtained are seven points of da'wah messages in the Aqidah category, five points of da'wah messages in the Sharia category and seven points of da'wah messages in the Akhlak category.